2021
DOI: 10.1145/3432932
|View full text |Cite
|
Sign up to set email alerts
|

Agency and Extraction in Emerging Industrial Drone Applications

Abstract: Rapidly diffusing 'industry 4.0' technologies stand to impact a broad range of stakeholders. Prior to implementation, forward looking formative analyses can identify systems and policy designs to promote equitable benefit. We investigate this potential through an analysis of stakeholders to a potential drone implementation on a small commercial farm in Rwanda. Translating stakeholders' imaginaries within a post-colonial frame, we identify hopes and concerns related to agency and influenced by global and local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…If new tools are to be integrated into vector control strategies, they need to be owned and operated by those delivering interventions. This is particularly pertinent with new technological equipment (including drones) that have historically been deployed from the global North into communities in the global South [ 41 ]. This study demonstrated that drone and smartphone technology can be owned and operated by the NCMP in Zanzibar through the collaboratively designed SIS framework, providing a model for other vector control programs.…”
Section: Discussionmentioning
confidence: 99%
“…If new tools are to be integrated into vector control strategies, they need to be owned and operated by those delivering interventions. This is particularly pertinent with new technological equipment (including drones) that have historically been deployed from the global North into communities in the global South [ 41 ]. This study demonstrated that drone and smartphone technology can be owned and operated by the NCMP in Zanzibar through the collaboratively designed SIS framework, providing a model for other vector control programs.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of Industry 4.0 technologies, like drones and IoT devices, has further expanded the stakeholder landscape in mechatronics. Hanrahan et al (2021) highlight the impact of these technologies on a broad range of stakeholders, emphasizing the need for equitable benefit distribution and local agency. In the context of industrial mechatronics, this translates to designing systems that are not only technologically advanced but also socially and ethically responsible.…”
Section: Stakeholder Analysis In Industrial Mechatronicsmentioning
confidence: 99%
“…Proprietary drone solutions usually require a significant initial investment, monthly software subscriptions, or an internet connection for cloud processing, which can constitute barriers for many low-resource users [ 19 , 20 ], and usually function as a ‘black-box’ which offer users little insight on its internal workings, and limited customization [ 21 ]. Also, when these solutions are implemented in developing countries, concerns have been raised regarding limited repairability, and risks of technological dependence and extractive practices [ 22 ].…”
Section: Introductionmentioning
confidence: 99%